AN ANALYSIS OF CLASSROOM INTERACTION IN AN ENGLISH CLASS: THE CASE AT ELEVENTH GRADE OF AN IMMERSION CLASS IN SMA NEGERI BALI MANDARA - ., Ni Putu Rika Amanda Putri; ., Drs. Asril Marjohan,MA; ., I G A Lokita P Utami, S.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Penelitian ini bertujuan untuk mengetahui kategori interaksi kelas pada kelas immersi dengan menggunakan Foreign Language Interaction (FLINT) system. FLINT system dibagi menjadi 22 kategori, yaitu: (1) Deals with Feeling, (2) Praise or Encouraging, (2a) Jokes, (3) Uses Ideas of Students, (3a) Repeats Student Response Verbatim, and (4) Asks Questions (5) Gives information, (5a) Corrects without Rejection, (6) Gives Directions, (6a) Direction Pattern Drills, (7) Criticizes Student Behaviour, and (7a) Criticizes Student Response (8) Student Response Specific, (8a) Student Response Choral, (9) Student Response Open-Ended or Student-Initiated, (10) Silence, (10a) Silence AV, (11) Confusion Work-Oriented, (11a) Confusion Non Work-Oriented, (12) Laughter, (13) Uses of the Native Language, and (14) Nonverbal. Penelitian ini dilaksanakan di kelas XI IPA I SMA Negeri Bali Mandara yang terdiri dari dua puluh dua siswa. Penelitian ini dirancang dengan menngunakan pendekatan deskriptif kualitatif. Terdapat lima instrument yang digunakan dalam penelitian ini yaitu, peneliti, kamera video, catatan lapangan, panduan wawancara dan daftar kategori.Data dikumpulkan dengan cara merekam interaksi kelas di kelas XI IPA I sebanyak empat kali. Kemudian, data ditranskrip dan dikategorikan berdasarkan FLINT system. Hasil analisis data menunjukan bahwa semua kategori interaksi kelas berdasarkan FLINT system terjadi di kelas. Jumlah interaksi yang dihasilkan oleh siswa 53.57 % sedangkan interkasi guru sebanyak 46.42%. Ini berarti bahwa interaksi guru dan siswa cukup seimbang dan siswa telah diberikan kesempatan terbaik untuk berpartisipasi di kelas.Kata Kunci : Kata kunci: Interaksi kelas, Foreign Language Interaction (FLINT) system, kelas immersi Abstract This study was aimed at finding the classroom interaction categories in an immersion class by using Foreign Language Interaction (FLINT) system. FLINT system is divided into 22 categories, namely: (1) Deals with Feeling, (2) Praise or Encouraging, (2a) Jokes, (3) Uses Ideas of Students, (3a) Repeats Student Response Verbatim, and (4) Asks Questions (5) Gives information, (5a) Corrects without Rejection, (6) Gives Directions, (6a) Direction Pattern Drills, (7) Criticizes Student Behaviour, and (7a) Criticizes Student Response (8) Student Response Specific, (8a) Student Response Choral, (9) Student Response Open-Ended or Student-Initiated, (10) Silence, (10a) Silence AV, (11) Confusion Work-Oriented, (11a) Confusion Non Work-Oriented, (12) Laughter, (13) Uses of the Native Language, and(14) Nonverbal. This study was conducted in XI Science I class of SMA Negeri Bali Mandara which consists of twenty two students. This study was designed by using descriptive qualitative approach. There were five instruments used in this study namely the researcher, video camera, observation sheet, interview guide and checklist. The data was collected by recording the classroom interaction in XI Science I class for four times. After that, the records were transcribed and categorized based on the FLINT system. The result of the data analysis shows that all categories of classroom interaction based on FLINT system occurred in classroom. The total interaction produced by the students was 53.57 % while the teacher produced 46.42%. It means that the interaction between teacher and students is quite balance and students are given best possible opportunity to participate in classroom. keyword : Keywords: Classroom interaction, Foreign Language Interaction (FLINT) system, Immersion class